Epidemiological and Clinical Aspects of Ulcerative Colitis in Mosul city, Iraq - Babakir-Mina, Muhammed (Kurdistan Journal of Applied Research, 2019)
Ulcerative Colitis (UC) is a chronic inflammatory disorder of the gastrointestinal tract with heterogeneous disease presentation. A cross-sectional descriptive study was undertaken in Mosul General Hospital. The study was conducted using two distinct methodologies. An observational checklist was used by the researcher to assess the patients’ characteristics and factors related to UC from 200 hospitalized patients from December 2018 to April 2019. Data were entered into spreadsheets and analyzed in Statistical Package for Social Sciences (SPSS) version 22. The results showed that 49.0% of patients was males and 51.0% was female; the mean age was 46.36 years old. Elderly stage (> 45 years of age) makes the highest proportion of the patients 99 (49.5%). The majority of patients was from urban or inside Mosul city center 140 (70%). The study also showed that the more frequency of patients 103 (51.5%) were in severe condition. Patients were used or given more antibiotics, they will be liked to get UC 191 (95.5%) and the relation was found to be statistically significant at (p<0.001). The study showed that 95 (47.5%) of all cases had a previous family history of UC. Out of 102 female patients, 45 (44.1%) were more frequently under uses of contraceptive pills. 60 (58.8%) of patients was in severe cases of UC and followed by moderate 35 (34.3%). Out of 103 severe cases, 60 of them were female. These differences were statistically significant at (p<0.05). In addition, out of 45 female patients were used oral contraceptive pills, 30 (66.7%) of them were in severe cases of UC and followed by 14 (31.1%) were in moderate cases. Majority of patients previously were sensitive to spices 160 (80.0%) and followed by fish and eggs 21 (10.5) 16 (8.0%) respectively. In addition, out of 160 spices sensitive patients, 80 (50.5%) of them were in severe cases and 61 (38.1%) were in moderate cases. Statistically, these differences are significant at (p<0.05). In conclusion, UC among late adult in our community needs critical care and monitoring. The female patients were at risk of UC especially, who uses oral contraceptive pills. The random and more antibiotic uses are considered as major risk factors lead to cause UC.